The recessive C locus in the MITF gene plays a key regulatory role in the plumage colour pattern of duck (Anas platyrhynchos). Issue 2 (4th March 2019) - Yang, L.; Mo, C.; Shen, W.; Du, X.; Akbar Bhuiyan, A.; Li, L.; Li, N.; Gong, Y.; Li, S.
ABSTRACT: 1. The c/c alleles are responsible for the white plumage colour of ducks; however, the gene corresponding to this locus is still unclear. In order to identify the locus-related candidate gene associated with duck's plumage colour pattern, it was necessary to analyse the whole genome resequencing data. 2. A total of 929, 465 SNPs in chromosome 13 and 1, 688 SNPs in the region of the Microphthalmia-Associated Transcription Factor ( MITF ) gene were identified from whole genome resequencing data analysis. After construction of an FST plot from chromosome 13, MITF was highlighted as a candidate gene, possessing the highest FST value (0.811) on chromosome 13. 3. Six novel SNPs were discovered, located in the intronic region of the MITF gene. F2 progeny of Kaiya × Liancheng ducks ( N = 1, 061) were selected for genotyping by the Restriction Fragment Length Polymorphism (RFLP) technique. Association analysis using Haploview software was used for validation of the results. 4. Association results between SNPs and phenotypes showed significant association with corresponding phenotypes. All the significantly associated SNPs were located in the identified candidate gene. 5. The identified candidate gene provided novel information which is important in marker-assisted selection and breeding of duck and for the investigation of the C locus recessive white genetic mechanisms underlying plumage colour pattern.